Pollination and Plant Resources Change the Nutritional Quality of Almonds for Human Health - Brittain, Claire; Kremen, Claire; Garber, Andrea; Klein, Alexandra-Maria (PloS one, 2014)
Insect-pollinated crops provide important nutrients for human health. Pollination, water and nutrients available to crops can influence yield, but it is not known if the nutritional value of the crop is also influenced. Almonds are an important source of critical nutrients for human health such as unsaturated fat and vitamin E. We manipulated the pollination of almond trees and the resources available to the trees, to investigate the impact on the nutritional composition of the crop. The pollination treatments were: (a) exclusion of pollinators to initiate self-pollination and (b) hand cross-pollination; the plant resource treatments were: (c) reduced water and (d) no fertilizer. In an orchard in northern California, trees were exposed to a single treatment or a combination of two (one pollination and one resource). Both the fat and vitamin E composition of the nuts were highly influenced by pollination. Lower proportions of oleic to linoleic acid, which are less desirable from both a health and commercial perspective, were produced by the self-pollinated trees. However, higher levels of vitamin E were found in the self-pollinated nuts. In some cases, combined changes in pollination and plant resources sharpened the pollination effects, even when plant resources were not influencing the nutrients as an individual treatment. This study highlights the importance of insects as providers of cross-pollination for fruit quality that can affect human health, and, for the first time, shows that other environmental factors can sharpen the effect of pollination. This contributes to an emerging field of research investigating the complexity of interactions of ecosystem services affecting the nutritional value and commercial quality of crops.